ISDC Feedback on Emerging Portfolio25 Draft - CGIAR Independent Science for Development Council (CGIAR Independent Science for Development Council, 2024)
The Independent Science for Development Council (ISDC) reviewed the “Draft Portfolio25 Document: A set of proposals on the CGIAR 2025-27 Research and Innovation.” Our review is organized by comments on the overall portfolio, followed by specific feedback for the three Action Areas. This document provides brief and high-level reflections for consideration in future portfolio development.